Conformational change of the Bordetella response regulator BvgA accompanies its activation of the B. pertussis virulence gene fhaB - David Kim; John Tracey; Manuel Becerra Flores; Kanita Chaudhry; Rafae Nasim; Abraham Correa-Medina; Leslie Knipling; Qing Chen; Scott Stibitz; Lisa M.M. Jenkins; Kyung Moon; Tim Cardozo; et al. (Computational and Structural Biotechnology Journal, 2022)
The BvgAS two-component system regulates virulence gene expression in Bordetella pertussis. Although precise three-dimensional structural information is not available for the response regulator BvgA, its sequence conservation with E. coli NarL and previous studies have indicated that it is composed of 3 domains: an N-terminal domain (NTD) containing the phosphorylation site, a linker, and a DNA-binding C-terminal domain (CTD). Previous work has determined how BvgACTD dimers interact with the promoter (PfhaB) of fhaB, the gene encoding the virulence adhesin filamentous hemagglutinin. Here we use molecular modeling, FeBABE footprinting, and crosslinking to show that within the transcription complex of phosphorylated BvgA (BvgA ∼ P), B. pertussis RNAP, and PfhaB, the NTDs displace from the CTDs and are positioned at specific locations relative to the three BvgA ∼ P binding sites. Our work identifies a patch of the NTD that faces the DNA and suggests that BvgA ∼ P undergoes a conformational rearrangement that relocates the NTD to allow productive interaction of the CTD with the DNA.